Computational Analysis of N-acetyl transferase in Tribolium castaneum - Singh, Kailash (Biomedical Informatics, 2013)
N-acetyl transferase (NAT) is responsible to catalyze the transfer of acetyl groups to arylamines from acetyl-CoA. Aralkylamine Nacetyl transferase (AANAT), which belongs to GCN5-related N-acetyl transferase member, is a globular 23-kDa cytosolic protein that forms a reversible regulatory complex with 14-3-3 proteins, AANAT regulates the daily cycle of melatonin biosynthesis in mammals, making it an attractive target for therapeutic control of abnormal melatonin production in mood and sleep disorders. There is no evidence available regarding α and β subunits, active site and their ASA value in Dopamine N-acetyl transferase. Therefore, we describe the development of Dopamine N-acetyl transferase model in Tribolium castaneum. We further document the predicted active sites in the structural model with solvent exposed ASA residues. During this study, the model was built by CPH program and validated through PROCHECK, Verify 3D, ERRAT and ProSA for reliability. The active sites were predicted in the model with further ASA analysis of active site residues. The discussed information thus provides insight to the predicted active site and ASA values of Dopamine N-acetyl transferase model in Tribolium castaneum.